Production and Characterization of Wine from Golden Delicious Apples using Saccharomyces Cerevisiae Isolated from Selected Nigerian Indigenous Alcoholic Beverages - Adesokan, Isaac Ayanniran (Journal of Food Technology Research, 2022)
There are many health benefits associated with consumption of apples and fermented apple juice, such as apple cider and apple wine. As a result of several health claims associated with the consumption of apple wine, this study was conducted with a view of producing apple wine using S. cerevisiae isolated from indigenous Nigerian alcoholic beverages. The aim is to develop indigenous technology for the production of apple wine and, by extension, tropical fruit wines. During the fermentation of apple juice into wine, changes in pH, titratable acidity (TA), brix/acid ratio (B/A), ascorbic acid (AA), total soluble solids (TSS), reducing sugars (RS), total sugars (TS), alcohol content (AC) and yeast count (YC) were determined using standard methods. The apple wine produced was rated by taste panelists using a 9-point hedonic scale. The following result ranges were obtained: pH (3.49–4.02), TA (18.0–43.2mg/ml), B/A (0.221–0889), AA (4.90–74.51mg/ml), TSS (9.0–18.0 mg/g), RS (0.260–0.347 mg/ml), TS (0.023–0.07mg/ml), AC (0.0–10.2%) and YC (7.40–11.99 log10cfu/ml). The sensory evaluation scores are appearance (7.14–7.71), flavor (6.71–8.00), mouth feel (7.00–8.00), taste (7.00–8.00) and overall acceptability (7.04–7.89). The apple wine that was fermented with Saccharomyces cerevisiae PAW02 (sample A) received the highest scores for flavor (7.8), mouth feel (8.00), taste (8.00) and overall acceptability (7.82). This sample also had the highest alcohol content of 10.2%. Therefore, this yeast strain (S. cerevisiae PAW02) could be explored for industrial production of alcoholic beverages from apples (apple wine).